THERMAL IMAGING DETEKSI KERUSAKAN DAUN PADA TANAMAN CABE - Lubis, Adyanata (Riau Journal Of Computer Science, 2020)
This study aims to implement pest detection using a camera so that it can see the point of leaf damage by pests in chili plants, the method used is thermal imaging technic, from observations and trials on chili plants there is image data from the detection period, the data is analyzed using thermal images so that it can spread the damage to pests of chili plants